Plano de comunicação dirigida: ONG formiguinhas valentes - Furlani, Bianca de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This report correponds to a Final Paper where it was developed a Directed Communication Plan to NGO Formiguinhas Valentes that act in the animal cause in Bauru. By doing a briefing and scenario analysis it was detected some mistakes about the communications process with their strategic public, they are the Bauru community, press, sponsors/partners and new volunteers. So setting general and specifics objectives it has been elaborated a Directed Communication Plan that intents to establish stronger relations between the organization and their public. For each kind of public it has been indicated acting plans and by these strategies it has been elaborated two products. By this way this work has four parts: planning, a directed educational hornbook for five to eight years old kids, a press kit to sponsors/partners and the final report.

Este relatório corresponde a um Trabalho de Conclusão de Curso no qual foi desenvolvido um Plano de Comunicação Dirigida à ONG Formiguinhas Valentes, atuante na causa animal em Bauru. Por meio de um briefing e análises de cenários, foram detectadas falhas referentes a processos comunicacionais com seus públicos estratégicos, sendo eles: comunidade bauruense, imprensa, patrocionadores/ parceiros e novos voluntários. Então, com o estabelecimento de objetivos gerais e específicos, foi elaborado um Plano de Comunicação Dirigida que visa fortalecer os vínculos da organização com tais públicos. Para cada um deles foram indicados planos de ação e, a partir dessas estratégias, dois produtos foram elaborados. Deste modo, este trabalho possui quatro partes: o planejamento, uma cartilha educativa dirigida a crianças de 5 a 8 anos, um press-kit dirigido a patrocionadores/parceiros e o relatório final.
Keywords: Comunicação; Organizações não-governamentais - Bauru (SP); Animais - Proteção; Planejamento estratégico; Communication